Gate Drive Circuit Suitable for a GaN Gate Injection Transistor - Fumiya Hattori; Yuta Yanagisawa; Jun Imaoka; Masayoshi Yamamoto (IEEE Access, 2023)
A GaN gate injection transistor (GIT) has great potential as a power semiconductor device. However, a GaN GIT has a diode characteristic at the gate-source, and a corresponding gate drive circuit is thus required. Several studies in the literature have proposed the gate drive circuits with the speed-up capacitors, but adding these capacitors complicates the gate drive circuit, and increases both the drive and reverse conduction losses. Moreover, driving a GaN GIT with such gate drive circuits becomes more susceptible to the false turn-on. In this paper, a gate drive circuit suitable for a GaN GIT without a speed-up capacitor is proposed. This type can provide the high-speed switching, and exhibit the low gate drive loss and reverse conduction loss. The proposed circuit also has high immunity against the false turn-on and stable gate-source voltage before and after startup. The drive loss of the proposed type is calculated and its validity is confirmed experimentally. Furthermore, the drive loss of the proposed type is compared with the conventional circuits. The result shows that the drive loss of the proposed type is improved by up to 50 %, compared with the conventional type. Finally, the proposed type is experimentally tested to drive a buck converter at the switching frequency of 150 kHz. The entire loss of the converter can be reduced by up to 9.2% at 250 W, compared with the conventional type.